PRELIMINARY STUDIES OF CERTAIN CHARACTERISTICS OF SPHERICAL FISHING FLOATS - Satyanarayana, A V V (Indian Journal of Fisheries, 2016)
Pieces of indigenous light wood are extensively employed for different types of nets in India. In the wake of introduction of modern fishing gear like trawl nets, bottom-set gill nets and purse seines, the need for glass, metallic and synthetic floats is increasingly felt at all the mechanised fishing centres. Although glass, aluminium alloy and synthetic floats are being manufactured in this country, no systematic attempt has so far been made to study the characteristics and fishing utility features of these Indian made floats. The present communication, which is only a preliminary account, is an enumeration of such a study. Comparison of some of the characteristics of floats manufactured in India with those of foreign countries has also been attempted.